A new carbon allotrope: T5-carbon. (December 2020) - Ding, Xian-Yong; Zhang, Chao; Wang, Dong-Qi; Li, Bing-Sheng; Wang, Qingping; Yu, Zhi Gen; Ang, Kah-Wee; Zhang, Yong-Wei
Graphical abstract: A novel carbon allotrope T5 -carbon is predicted by using first-principles calculations. It has a Vickers hardness of 76.5 GPa, which is lower than that of diamond but larger than those of T-carbon and cubic boron nitride. The reason for the slight lower Vickers hardness of T5 -carbon in comparison with diamond can be ascribed to the weaker bonding strengths in the carbon tetrahedron. Abstract: A novel carbon allotrope is predicted by first-principles calculations. This allotrope is obtained by replacing one of the two atoms in the primitive cell of diamond with a carbon tetrahedron, thus it contains five atoms in one primitive cell, termed T5 -carbon. The stabilities of T5 -carbon are checked in structural, thermal and vibrational calculations. T5 -carbon is a wide band gap semiconductor with an indirect band gap of 4.30 eV, and has a lattice thermal conductivity of 409 W/mK. Mechanical analyses reveal that T5 -carbon shows good mechanical performances. Furthermore, by modifying T5 -carbon with replacing some carbon atoms with Si or Ti atoms, we can obtain SiC4 or TiC4 structures. Importantly, the TiC4 system has a moderate conduction and valance band edges, comparable larger absorption capacity of visible light and smaller effective masses of electron and hole carriers than TiO2, confirming its photocatalysis applications.